Digital analytics as a driver of green brand competitive advantages - Kryvych, Yana; Lutsenko, Iryna; Vakula, Yana (Herald of Economics, 2025)
Introduction. In today’s conditions of transformation of global markets, driven by digitalization and growing environmental challenges, companies are forced to rethink approaches to building their own competitiveness. Green branding is taking an increasingly important place in strategic business development, and digital analytics is becoming a key tool that allows combining environmental values with effective marketing solutions.Purpose. The purpose of the article is to determine the impact of digital analytics on the formation and strengthening of the competitive advantages of a green brand by analyzing the dynamics of the digital presence and behavioral indicators of the company Ukono.Results. Bibliometric analysis has shown growing scientific attention to the combination of digital analytics and green branding, highlighting areas related to consumer behavior, the formation of green brand equity and the consequences of greenwashing. A comparative assessment of green brands Ukono, HempFactor and JoHemp revealed significant differences in the use of digital channels, in particular in the field of paid advertising, video content and the effectiveness of social interaction. Analysis of digital sales funnels and communication styles showed different levels of strategic maturity: from transactional to consultative and educational-value approach. The totality of the data obtained demonstrates that the effectiveness of the use of digital analytics directly determines the quality of market visibility and competitiveness of a green brand.Conclusions and prospects. The study confirms that digital analytics is a critical factor in strengthening the competitive advantage of green brands in a dynamic digital environment. It provides not only a deeper understanding of consumer behavior, but also forms strategic approaches to communication, value creation and avoiding reputational risks. Therefore, the integration of analytical data into marketing processes is becoming a determining condition for the sustainable development of environmentally oriented companies.